Merancang Media Hiburan Buku Cergam Menjadi Media Belajar untuk Alat Bantu Komunikasi - Nurhaida, Ida; Junaidi, Akmal; Hariyanto, Sugeng P; Syah, Pairul (FIkom Unisba, 2007)
For the sake of reinforcing the local knowledge (that seems to be abandoned by local community of West Lampung themselves) and to make corrections against agroforestry malpractices as well as of accommodating to the poor performance of extension programs on recharge area of West Lampung (including of media lacking of extension), we have developed the entertainment media of pictorial story books of coffee agroforestry. The media were designed especially for the low literate community (Nurhaida et al., 2004) to affirm the tao of knowledge of the four tribes dwell in the recharge area: Lampungese, Semendonese, Sundanese and Sundanese of villages of Way Mengaku, Sukananti, Sidomakmur and Gunung Terang respectively (see Nurhaida et al., (2005). There are four languages edition in accordance with the locally mother tongues of the four tribes plus Indonesian to accommodate the other tribes exist in West Lampung. Desk activities were conducted at the Laboratory of Multimedia, Departmentof Communication Science, The University of Lampung Indonesia. Media pretesting were conducted twice in August-September 2005 to measure the variables of attraction, self involvement, acceptability and comprehension of the media in accordance with Bertrand’s suggestion (1978). Between the two and the second of the media pretesting, there had been conducted the media improvements. The research showed that the entertainment media have been used up to be a learning media for the propose of extension program in the recharge area successfully. This claim is supported by the high effectiveness of the five editions: (Lampungese, Semendonese, Javanese, Sundanese and Indonesian of 85, 89, 88, 89, and 86% repectively) that brookthrough aggaints the severely heavied barrier of low litteracy : 27, 44, 39, 77, dan 88 words per second respectively. It is strongly recommended that: (1) reproduce the media and disseminate into community dwell on the recharge of West Lampung to reinforce the tao of knowledge, and (2) conduct the similar research on other recharge areas.